2012
DOI: 10.1016/j.ijhydene.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical considerations on the modelling of transport in a three-phase electrode and application to a proton conducting solid oxide electrolysis cell

Abstract: Theoretical considerations on the modelling of transport in a three-phase electrode and application to a proton conducting solid oxide electrolysis cell. International Journal of Hydrogen Energy, Elsevier, 2012, 37 (16) The paper presents a complete numerical model for the prediction of mass and charge transfer inside electrolysis cells and fuel cells working at high temperature and using cermets as electrodes. It also discusses some assumptions taken in fuel cells or electrolysis cells modelling.I think that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…This model showed a good agreement with a previous 3D numerical model [13] but needs to be confronted to experimental results for both SOFC and SOEC configuration. Once the model is validated, we will extend the study of the analytical model to assess the effective resistivity of the electrode and the generated heat source in each element of the MEA as a function of a dimensionless parameter named A.…”
Section: Introductionsupporting
confidence: 66%
“…This model showed a good agreement with a previous 3D numerical model [13] but needs to be confronted to experimental results for both SOFC and SOEC configuration. Once the model is validated, we will extend the study of the analytical model to assess the effective resistivity of the electrode and the generated heat source in each element of the MEA as a function of a dimensionless parameter named A.…”
Section: Introductionsupporting
confidence: 66%
“…It should be noted that at this content of NiO the percolation effect of a sharp reduction in the polarization resistance of the electrodes is initiated [328][329][330]. A theoretical study of the influence of other parameters (the size of the Ni-powder and the electrolyte particles in the anode mixture, volume phase fraction) can be found in the work of Völker and McMeeking [331], and Dumortiera et al [332]. It should be noted however, that the Ni-electrolyte cermets have a number of drawbacks, such as:…”
Section: Cathodementioning
confidence: 94%
“…Moreover, the reaction is generally supposed to occur in an active layer close to the interface with the electrolyte [5,23]. However, our team [40] previously showed that this assumption is valid under certain conditions : low ionic conductivity of ceramics, no limitation in the diffusion of species inside the electrode, metal grains radius not too large compared to ceramic grain radius. Our previous model also allowed predicting reaction profiles inside the electrodes.…”
Section: Fig 1 -Principle Of a Proton Conducting Solid Oxide Electromentioning
confidence: 99%
“…The assumptions for the establishment of this equation are checked with regards to the results of the literature. In the second part, the model is completed with a continuity equation set developed previously by our group for the description of transport phenomena inside a proton conducting high temperature electrolyzer [40]. Few models have investigated on the thermal management of solid oxide electrolyzer [11,20,29], therefore the proposed model is tested throughout a parametric analysis inside the PEN of a proton-conducting cell in galvanostatic mode.…”
Section: Fig 1 -Principle Of a Proton Conducting Solid Oxide Electromentioning
confidence: 99%
See 1 more Smart Citation